Autopsy Analysis of Renal Lesions: A Histomorphological Perspective (Journal of Forensic Medicine & Toxicology, 2025)
Objectives: The study aimed to evaluate the histomorphological spectrum of renal lesions in autopsy cases to determine  the prevalence and distribution of renal pathologies among individuals who died suddenly and unexpectedly. Material and Methods: This cross-sectional, observational study was conducted over one year in the Department of  Forensic Medicine and Toxicology at Government Medical College, Amritsar. A total of 160 autopsy cases were included,  excluding those with autolyzed kidneys. Detailed gross and histopathological examinations were performed on all kidney  samples, with additional PAS staining employed as necessary. Data on age, sex, and circumstances of death were recorded,  and findings were statistically analysed using SPSS software. Results: Among the 160 cases, 70.3% exhibited histopathological abnormalities. Acute pyelonephritis was the most  common lesion (24.975%), followed by acute tubular necrosis (14.85%). Glomerular sclerosis was observed in 11.25% of  cases, and renal cell carcinoma in 2.7%. A male predominance was noted, with the highest frequency of renal pathologies  in the 41-60 years age group. Gross examination revealed congestion in 61.25% of kidneys and cystic changes in 36.45%. Conclusion: The study underscores the significant incidence of renal pathologies, many of which remain undiagnosed  during life, particularly among middle-aged males. The findings emphasize the critical role of autopsy in detecting occult  renal conditions, offering insights that could improve the management and prevention of renal diseases
Keywords: Renal lesions; Histopathology; Autopsy study